2003
DOI: 10.1063/1.1625419
|View full text |Cite
|
Sign up to set email alerts
|

Focusing of surface-acoustic-wave fields on (100) GaAs surfaces

Abstract: Focused surface-acoustic waves ͑SAWs͒ provide a way to reach intense acoustic fields for electroand optoacoustic applications on semiconductors. We have investigated the focusing of SAWs by interdigital transducers ͑IDTs͒ deposited on ͑100͒-oriented GaAs substrates. The focusing IDTs have curved fingers designed to account for the acoustic anisotropy of the substrate. Different factors that affect focusing, such as the aperture angle and the configuration of the IDT fingers, were systematically addressed. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 29 publications
3
47
0
Order By: Relevance
“…The focusing IDTs were designed for an operation wavelength SAW = 5.6 m ͑corresponding to a resonance frequency of approximately 520 MHz͒ following the procedure discussed in detail in Ref. 8. These IDTs generate a SAW beam with full width at half maximum ᐉ Ϸ 15 m that are collimated over hundreds of microns.…”
mentioning
confidence: 99%
“…The focusing IDTs were designed for an operation wavelength SAW = 5.6 m ͑corresponding to a resonance frequency of approximately 520 MHz͒ following the procedure discussed in detail in Ref. 8. These IDTs generate a SAW beam with full width at half maximum ᐉ Ϸ 15 m that are collimated over hundreds of microns.…”
mentioning
confidence: 99%
“…16 In the focusing devices, the fingers are curved in order to produce a converging SAW beam. Further details about the focusing IDTs can be found in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned previously, these IDTs have curved fingers with a shape following curves of constant SAW group velocity. 16 Due to the acoustic anisotropy inherent of crystalline materials, the design of focusing IDTs relies on the precise knowledge of the dependence of the SAW properties on the propagation direction. 16 In SF IDTs, the latter also depends sensitively on the dimensions of the metal grating (Fig.…”
Section: Focusing Performancementioning
confidence: 99%
“…There is a simple and direct relation between the slowness curve and the wave surface, v g ͑ ͒ = ͓s͑ ͒cos͑ ͔͒ −1 , with as the beam-steering angle and = + . 2,3 Accurate knowledge of the slowness curve is needed in the design of SAW devices, as illustrated by tailored interdigital transducers ͑IDTs͒ that can focus a SAW beam 4 or even create a subwavelength acoustic source. 5 Wickramasinghe and Ash 6 showed that SAW slowness curves can be measured using a phase sensitive laser probe.…”
Section: Materials Anisotropy Unveiled By Random Scattering Of Surfacementioning
confidence: 99%